Fetal growth at different gestational periods and risk of impaired childhood growth, low childhood weight and obesity: a prospective birth cohort study. (6th April 2021) - He, J‐R; Ramakrishnan, R; Wei, X‐L; Lu, J‐H; Lu, M‐S; Xiao, W‐Q; Tu, S; Liu, X; Zhou, F‐J; Zhang, L‐F; Xia, H‐M; Qiu, X
Abstract : Objective: To examine the longitudinal associations of fetal growth with adverse child growth outcomes and to assess whether maternal metabolic factors modify the associations. Design: Prospective cohort study. Setting: Born in Guangzhou Cohort Study, China. Population: A total of 4818 mother–child pairs. Methods: Fetal growth was assessed according to estimated fetal weight (EFW) from 22 weeks of gestation until birth and the measurement of the birthweight. Fetal growth Z ‐scores were computed from random effects in the multilevel linear spline models to represent fetal size in early pregnancy (22 weeks of gestation) and growth in mid‐pregnancy (22–27 weeks of gestation), early third trimester (28–36 weeks of gestation) and late third trimester (≥37 weeks of gestation). Main outcome measures: Z ‐scores for childhood stunting, low weight, overweight or obesity, length/height for age (LAZ/HAZ), weight for age (WAZ) and body mass index for age (BMIZ) at the age of 3 years. Adjusted associations were examined using multiple Poisson or linear regression models. Results: Increased Z ‐scores of fetal size in early pregnancy and growth in mid‐pregnancy and early third trimester were associated with a higher risk of childhood overweight or obesity (risk ratios 1.25–1.45). Fetal growth in each period was negatively associated with stunting and low weight, with the strongest associations observed for fetal size in early pregnancy and growth in mid‐pregnancy. The results for continuous outcomes (LAZ/HAZ, WAZ and BMIZ) were similar. The associations of fetal growth with overweight or obesity in childhood were stronger among mothers who were underweight and who were overweight or obese than among mothers of normal weight. Conclusions: Accelerated fetal growth before 37 weeks of gestation is associated with children who are overweight or obese, whereas the critical period for stunting and low weight occurs before 28 weeks of gestation. Tweetable abstract: Fetal growth during different periods is differentially associated with childhood stunting, underweight and overweight or obesity. Tweetable abstract: Fetal growth during different periods is differentially associated with childhood stunting, underweight and overweight or obesity.